IMPROVEMENT OF PRODUCT QUALITY IN THE AI ECONOMY: HUMAN KNOWLEDGE VS. DIGITAL TECHNOLOGIES - Anastasia A. Sozinova; Olga A. Glushko; Anastasia A. Kurilova; Vera I. Menshchikova (International Journal for Quality Research, 2023)
This paper is a comparative study of the advantages of the influence of implementing digital tools and the quality of human knowledge on the improvement of product quality. We substantiate the role of the human factor in the formation of competitive knowledge that is necessary for implementing ambitious goals of companies in the achievement of competitive advantages in the sphere of continuous improvement of product quality. We also prove the necessity for supporting the level of human knowledge competitiveness, which will facilitate the increase in product quality and social justice (employment level). To reach the goals of this research, we use the index method, comparative analysis and cause-effect relationships method. The novel aspect of this paper is connected with the determination of the specifics and advantages of using the quality of human knowledge and digital technologies for achieving the goals of the growth of product quality, which allows forming the current directions for the creation of efficient solutions for further industrial growth.